2014
DOI: 10.1021/ma501520u
|View full text |Cite
|
Sign up to set email alerts
|

Field-Cycling NMR Relaxometry Probing the Microscopic Dynamics in Polymer Melts

Abstract: Field-cycling (FC) 1H and 2H NMR relaxometry is applied to linear polybutadiene (PB) of different molar mass (M) in order to test current polymer theories. Applying earth field compensation, five decades in the frequency dependence of the spin–lattice relaxation rate T 1 –1(ν) = R 1(ν) are accessed (200 Hz - 30 MHz), and we focus on the crossover from Rouse to entanglement dynamics. A refined evaluation is presented, which avoids application of frequency–temperature superposition as well as Fourier transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 56 publications
(195 reference statements)
12
60
1
Order By: Relevance
“…Departures of w 0 0 NMR trends from this function, observed at temperatures much higher than T g , have been ascribed to contributions to relaxation arising from slower collective polymer dynamics. 21,[52][53][54][55][56] Hence, in our case the obtained values of a indicate that the collective dynamics does not significantly contribute to relaxation, most probably because the measurements were performed only up to 50 K above the glass transition. Since glassy dynamics is not influenced by the chain length, 21 the polymer polydispersity is expected to play a minor role.…”
Section: H Ffc Nmr Relaxometrysupporting
confidence: 50%
“…Departures of w 0 0 NMR trends from this function, observed at temperatures much higher than T g , have been ascribed to contributions to relaxation arising from slower collective polymer dynamics. 21,[52][53][54][55][56] Hence, in our case the obtained values of a indicate that the collective dynamics does not significantly contribute to relaxation, most probably because the measurements were performed only up to 50 K above the glass transition. Since glassy dynamics is not influenced by the chain length, 21 the polymer polydispersity is expected to play a minor role.…”
Section: H Ffc Nmr Relaxometrysupporting
confidence: 50%
“…At 303 K, all samples show NMRD curves with a power law dependence on frequency ( R 1 (ω) ∝ ω –γ ) at lower frequencies (γ = 0.16–0.18) and a dispersion at higher frequencies. The observed exponents are similar to those reported in the literature for high-molar-mass ( M > M e ) polyisoprene 64 66 , 68 70 , 85 and IR rubbers, 73 and can be ascribed to the Rouse regime (regime I of the TR model), while the dispersion corresponds to glassy dynamics (regime 0). Small differences were found between the NMRD curves of filled rubbers and that of IR_S2.…”
Section: Resultssupporting
confidence: 87%
“… 46 48 , 61 Since glassy dynamics is strongly prevalent over polymer dynamics, 44 the latter can only be correctly investigated after separation of these two components in FC NMR data, as pointed out by Rössler and co-workers. 45 , 47 , 62 68 …”
Section: Introductionmentioning
confidence: 99%
“…4,13,23 Applying these procedures for polymers a picture emerged which confirms the tube-reptation model only in parts. 8,13 Recently, we also investigated the dynamics of poly-(propyleneimine) (PPI) dendrimer of different generations by different techniques. 19 The bulk dendrimer constitutes highly viscous liquids at room temperature that undergo a glass transition with a glass transition temperature T g of around 200 K, virtually independent of the number of generations.…”
Section: Introductionmentioning
confidence: 99%
“…We note that, neglecting the intermolecular term, eq 4 was tested previously, 22,24 but succeeding experiments revealed that the intermolecular relaxation has to be taken into account, in particular, when low-frequency dispersion is discussed. 8,12,13 Next, we define the cumulative mode ratio F NMR (N):…”
Section: Introductionmentioning
confidence: 99%